Comparison of shear bond strength of amalgam bonded to primary and permanent dentin - Mahdi S; Bahman S; Arghavan A; Fatemeh M (Wolters Kluwer Medknow Publications, 2008)
Amalgam′s non-adhesive characteristics necessitate cavity preparations incorporating retentive features, which often require the removal of non-carious tooth structure. Use of adhesives beneath amalgam restorations, would be helpful to overcome this disadvantage. This study was undertaken to compare the mean shear bond strength of amalgam bonded to primary and permanent dentin, to evaluate the efficacy of amalgam adhesives in pediatric dentistry.27 primary and 28 permanent posterior teeth with intact buccal or lingual surfaces were grounded to expose dentin and wet-polished with 400-grit silicone carbide paper. Scotchbond Multi Purpose Plus adhesive system was applied to the dentin surfaces and light cured. Amalgam was condensed onto the treated dentin through a plastic mold.shear bond strength testing was done using an Instron Universal testing machine, at a crosshead speed of 0.5 mm/min.The data were analyzed by independent samples t-test The difference among the two groups was not statistically significant (p>0.05) Bonded amalgam showed the same level of bond strength to primary and permanent dentin; so, application of amalgam bonding agents in pediatric dentistry can be recommended.